Sustainability from Social Commitment to Tourist Attraction: Terminological Approach to European Green Capitals Brochures - Emanuela Ammendola (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2022)
The tourism industry currently represents a relevant sector of the international market and a fundamental resource for countries like European ones, which offer a heterogeneous mosaic of histories and cultures. Such sector is, however, characterized by an ever-changing nature depending on the constantly evolving needs, habits, and awareness of different types of travelers. Far from investigating the largely discussed concept of sustainable tourism, this article aims to examine from a linguistic perspective the concept of urban sustainability as a tourist attraction in the context of the European Green Capitals Award (EGCA) and the relative terminological effects on the language of tourism. A corpus-driven approach was used to quantitatively and qualitatively investigate the terminology used in the brochures of the European Green Capitals selected from 2010 to 2021, which are included in the section Environment of the European Commission website. Following a quantitative analysis of the data, a qualitative analysis was conducted to interpret the meaning and the degree of technicality of the sustainability-related terms used in the corpus and their potential employment in the field of tourism. The corpus analysis was intended to provide evidence of those new linguistic structures used in texts like EGCA brochures which, being addressed to a wide range of readers, may directly or indirectly influence tourist interests and tourism promotional language as well.